"I'm not racist but I expect linguistic assimilation": The concealing power of humor in an anti-racist campaign. (June 2018) - Archakis, Argiris; Lampropoulou, Sofia; Tsakona, Villy
Highlights: We focus on an antiracist campaign that attempts to stigmatize discrimination against immigrants in Greece. The representation of immigrant and majority voices promotes an ideology of ethnic monolingualism. Humor exposes overt racist attitudes but conceals covert assimilationist discourses. The fictional data under investigation end up enlarging the continuum of racist discourse. Abstract: Immigration that has taken place from early 1990 onwards is said to contribute to the development of a globalized landscape where strict ethnic boundaries and traditional social delineations have become fuzzy (Blommaert and Rampton, 2011). This study investigates the formation and (re)negotiation of widespread social stereotypes and language ideologies concerning immigrants and their use of Greek in fictional data. We investigate an online antiracist campaign that officially aims to dissolve the disclaimer "I'm not racist but…". We specifically analyze three antiracist clips uploaded on YouTube representing encounters between majority members and immigrants. We focus on humor through which antiracist messages are aimed to be communicated to the public. Our findings confirm that although humor is exploited so as to expose and stigmatize racist practices, the data under scrutiny end up reproducing the ideology of ethnic monolingualism. Through an analysis of the linguistic and stylistic resources assigned to the represented characters, we reveal the deeply entrenched indexical order of the Greek language monopoly which goes hand in hand with racist attitudes. To this end, the disclaimer "we stigmatize racism, but we expect immigrants to assimilate to our language and culture" arises, thus, broadening the spectrum of racist discourses.